Spray- or freeze-drying of casein micelles loaded with Vitamin D2: Studies on storage stability and in vitro digestibility. (November 2018) - Moeller, Henrike; Martin, Dierk; Schrader, Katrin; Hoffmann, Wolfgang; Lorenzen, Peter Chr.
Abstract: Casein micelles (CM) loaded with Vitamin D2 (Vit. D2) were spray- and freeze-dried at pilot scale. The powders showed constant Vit. D2 contents over four months of storage. The CM structure was retained after processing and drying. Low fat yoghurt was enriched with the spray-dried powder or with free Vit. D2. An in vitro proteolysis showed that 90% of the Vit. D2 added as an encapsulated product, e.g. dried CM, remained active compared to only 67% when Vit. D2 was supplemented as a free substance. Since all proteins were hydrolysed after in vitro proteolysis, it can be assumed that the Vit. D2 contents determined would be ultimately available in the lumen. Highlights: Casein micelles isolated by microfiltration can be loaded with Vitamin D2 at pilot scale. Vitamin D2 loaded casein micelles can be spray- and freeze-dried at pilot scale. Vitamin D2 content keeps constant over four months of storage. Low-fat yoghurt as a model system was successfully enriched with loaded and spray-dried CM. An in vitro digestion showed 90% of the encapsulated Vitamin D remained after proteolysis.